Single residue substitution at N-terminal affects temperature stability and activity of L2 lipase - Bukhari, Noramirah; Leow, Adam Thean Chor; Raja Abdul Rahman, Raja Noor Zaliha; Mohd Shariff, Fairolniza (MDPI AG, 2020)
Rational design is widely employed in protein engineering to tailor wild-type enzymes for industrial applications. The typical target region for mutation is a functional region like the catalytic site to improve stability and activity. However, few have explored the role of other regions which, in principle, have no evident functionality such as the N-terminal region. In this study, stability prediction software was used to identify the critical point in the non-functional N-terminal region of L2 lipase and the effects of the substitution towards temperature stability and activity were determined. The results showed 3 mutant lipases: A8V, A8P and A8E with 29% better thermostability, 4 h increase in half-life and 6.6 °C higher thermal denaturation point, respectively. A8V showed 1.6-fold enhancement in activity compared to wild-type. To conclude, the improvement in temperature stability upon substitution showed that the N-terminal region plays a role in temperature stability and activity of L2 lipase.